2017
DOI: 10.4238/gmr16039775
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Plathymenia reticulata Benth. in fragments of Atlantic Forest in southeastern Brazil

Abstract: Studies of genetic diversity in natural populations are important for the definition of conservation strategies, especially in populations reduced by processes of fragmentation and continuous forest extraction. Molecular markers stand out as interesting tools for these studies. The objective of this research was to characterize the diversity and genetic structure of Plathymenia reticulata (Fabaceae), occurring in two fragments of the Montana Semideciduous Forest in the southern of Espírito Santo State, Brazil,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…However, this estimate corresponds to the historical gene flow, referring to the interaction of populations in the past, when the actual adult trees settled (Kageyama et al, 2003). Nevertheless, the N m value found in this study can be considered low when compared to the values described for other tree species, such as 12.70 for Plathymenia reticulata (Souza et al, 2017) and 13.54 for Senefeldera verticillata (Vieira et al, 2018), which may be favoring the moderate genetic differentiation between populations.…”
Section: Genetic Structuringcontrasting
confidence: 86%
See 1 more Smart Citation
“…However, this estimate corresponds to the historical gene flow, referring to the interaction of populations in the past, when the actual adult trees settled (Kageyama et al, 2003). Nevertheless, the N m value found in this study can be considered low when compared to the values described for other tree species, such as 12.70 for Plathymenia reticulata (Souza et al, 2017) and 13.54 for Senefeldera verticillata (Vieira et al, 2018), which may be favoring the moderate genetic differentiation between populations.…”
Section: Genetic Structuringcontrasting
confidence: 86%
“…The satisfactory levels found for the genetic diversity of the species indicate that it has managed to keep up with the disturbances generated by its predatory exploitation and the fragmentation of natural populations, having as a positive factor the fact that they are located in CU's, which restrict selective cutting. Studies with vulnerable and threatened species, such as D. nigra, demonstrated that these species can restore their population, if there is genetic diversity, knowledge and, control over the genetic structure in the occurrence areas (Martinelli and Moraes, 2013;Souza et al, 2017;Mangaravite et al, 2019). This is even more relevant because D. nigra is an allogamous species, that is, it preferably performs cross-fertilization benefited by entomophilous pollination, consequently increasing the genetic diversity.…”
Section: Cernementioning
confidence: 99%
“…The destruction of natural sites in which tree species belong may often produce a disequilibrium in ecological interactions with pollinators (Mendes et al, 2022) and seed dispersers (Giombini et al, 2009). Studies that have addressed the current genetic diversity of allogamous tropical tree species through molecular markers frequently found high or moderate levels of genetic variation in natural populations (Collevatti et al, 2014, Souza et al, 2017, Muniz et al, 2022. But also becoming more common are studies documenting signi cant reduction in genetic diversity and changes in the genetic structure of populations when comparing conserved forests with sites that underwent habitat loss (Muniz et al, 2022) and fragmentation (Vranckx et al, 2012, González et al, 2020.…”
Section: Introductionmentioning
confidence: 99%